Isotopic Composition of Water Bodies in the Kuiseb and Cuvelai-Etosha Basin, Namibia - Uugwanga, M.N; Kgabi, N.A; Knoeller, K.; Motsei, L. (Namibian Journal for Research, Science and Technology, 2018)
This study aimed to investigate the isotopic composition of different water bodies in two basins. Water samples collected from open and undefined water sources such as the Etaka and Ruacana waterfall and an artificial spring in the Cuvelai-Etosha Basin; as well as the boreholes, Atlantic Ocean and fog from the Kuiseb Basin were analysed for stable isotopes namely, Deuterium (δ2H) and oxygen 18 (δ18O)) and elemental composition. Stable isotope ratios were measured using the Picarro L2120–i Analyser (Cavity Ring-Down Spectrometry method) and trace elemental composition was assessed using the Inductively Coupled Plasma Mass Spectroscopy (ICP-MS). Open water bodies of the Cuvelai-Etosha Basin were found to be enriched with heavy isotopes, and also plotted along the evaporation line (below and away from the Global Meteoric Water Line (GMWL)), which is indicative of the high evaporation rates within the basin. Kuiseb boreholes were depleted of heavy isotopes and plotted along the Global and Local Meteoric Water Line, indicating direct recharge from precipitation and minimal, if any, evaporation effects. Trace elemental analyses indicated possible contamination of water bodies with high concentrations of Al and Fe, confirming the effect of sediment input in the flood prone basin (Cuvelai), and continual erosion/hard crust in the Kuiseb. Positive correlations with r2 greater than 0.5, confirming increase in δ18O and δ2H with increase in trace elements including Strontium and Lithium in the Kuiseb Basin, and Molybdenum (Mo) and Manganese (Mn) in the Cuvelai-Etosha Basin were also observed.